PENGARUH KEPEMIMPINAN, REWARD, DAN PUNISHMENT TERHADAP KINERJA KARYAWAN (STUDI PADA PT. BANK MANDIRI PERSERO TBK KANTOR CABANG PEMBANTU SEMARANG PANDANARAN) - Mochammad Firza Anvialdi; Reni Shinta Dewi; Hari Susanta Nugraha (Universitas Diponegoro, 2026)
Abstract: Organizational behavior theory is a major part of the field of organizational research, as behavioral reasoning is found in a variety of theoretical approaches. This research aims to determine the influence of leadership, reward and punishment policies on employee work productivity. This research is a quantitative research using probability sampling with a saturated sampling technique or taking all members of the population, including 50 respondents, employees of Bank Mandiri, Semarang Branch Office. Instruments in the form of questionnaires were used for data collection, and multiple linear regression analysis was used to test hypotheses. The research results show that there is a positive and significant influence of leadership, reward and punishment on employee performance, either partially or simultaneously. Suggestions for future research could be to use a larger sample size by involving other companies from various business sectors, and the use of variables that predict performance needs to be increased (more than 3 variables) to produce higher accuracy of the prediction model.Keywords: Leadership; Reward; Punishment; Employee Performance